Pengaruh Kinerja Lingkungan, Kinerja Sosial dan Mekanisme Tata Kelola Terhadap Kinerja Keuangan Pada Perusahaan Go Public di Indonesia - Susanti, Elyssa; Hindasah, Lela (AKUNTANSI DEWANTARA, 2025)
This study aims to examine the impact of environmental performance, social performance, and governance mechanisms on the financial performance of publicly listed companies in Indonesia during the 2019–2023 period. Utilizing 245 firm data, the analysis was conducted using multiple linear regression with a fixed effect model approach. The findings reveal that environmental performance has a negative and significant impact on financial performance, indicating that the high costs of meeting strict environmental standards may suppress profitability. Conversely, social performance has a positive and significant impact on financial performance, demonstrating that corporate social responsibility contributes to enhanced reputation and operational efficiency. Institutional ownership negatively and significantly affects financial performance, possibly due to short-term pressures from institutional investors. In contrast, foreign ownership positively and significantly influences financial performance, reflecting benefits such as technology transfer, improved managerial expertise, and access to international markets. Meanwhile, the presence of independent commissioners does not significantly affect financial performance, which may be attributed to limited supervisory effectiveness. This study contributes to understanding the dynamics between environmental, social, and governance performance and financial performance, offering practical implications for managerial decision-making.mechanisms and improved independence in decision-making.